Personality and self-concept according to the cultural background of primary education students - Mohamed Al-Lal Mohand; Lucía Herrera Torres; Laila Mohamed Mohand (INFAD, 2017)
This work aims to analyze the personality and self-concept of Primary Education students according to their cultural background. For this purpose, 422 students from Primary Education (46.9% boys and 53.1% girls) participated in the study, which were studied fifth (n = 204) and sixth year (n = 218). The instruments used were the Test of Self-Concept Form 5 (AF-5) and the Short Form Big Five Questionnaire for Children (S-BFQ-C). The results showed differences in AF-5 by cultural brackground. Thus, the children of Amazigh cultural background scored higher in the physical self-concept than those of European cultural origin. No differences in the different personality factors were found agree with that variable.